Wood fungi and epiphytic lichens in Swedish boreal woodland key habitats in relation to stand and landscape variables - Jonsson, Bengt Gunnar; Atrena, Anita; Edman, Mattias; Carlsson, Fredrik; Englund, Oskar; Undin, Malin (Mid Sweden University, 2026)
Database Title

Wood fungi and epiphytic lichens in Swedish boreal woodland key habitats in relation to stand and landscape variables

General information

This data set was collected as a part of PhD-student project resulting in two scientific publication (Atrena et al. 2025; 2026) and a PhD-thesis (Atrena 2025). Below follows information on the different tables included in the Access database. In the database all variables in the tables are explained concerning the type of variable and when relevant includes measurement unit.

The field data was collected during two field campaigns. The first included inventories of transects in the woodland key habitats where stand data and occurrence of fungal fruitbodies on decaying logs was collected. Fungal sampling was done during 2022 (August - September). In addition, drill samples for DNA-primer analysis were collected on a subset of the logs along the transects. In the second field campaign, full stand inventories of wood fungi and epiphytic lichens were performed but in the analysis the same set of independent variables were used. Fungal and lichen sampling was done during 2023 (August - September). Further details are provided in the published articles and PhD-thesis, all open access.

List of tables [listed as they occur in the database]

Table Fungi_DNA

Provides the occurrence of species identified on individual logs from DNA primers including 10 unique species of which 9 was used in the analyses. Phellinidium ferrugineofuscum; Steccherinium collabens; Leptoporus mollis; Cystostereum murrayi; Fomitopsis rosea; Amylocystis lapponica; Skeletocutis odora; Phellopilus nigrolimitatus; Phlebia centrifuga; Antrodia serialis (not used in the analysis).

Table Fungi_Stand

The presence of fungi species during full stand inventory. For redlisted species, numbers represent number of observations in each stand occurrences while for non-redlisted species only presence is provided (1).

Table Fungi_Traits

The full names of fungal species, their threat status (Artdatabanken 2020), decay strategy (rot type), fruitbody persistence and spore volume

Table Fungi_Transect

The occurrence of fungi on individual logs from the transect study.

Table Landscape data (used)

Data for the surrounding landscape presented as % of respective landscape variable except for “area40 and area 70 which represent the area (ha) of connected medium and high quality forests calculated based on mapping of high conservation value forests in Sweden (Bubnicki et al. 2024).

Table Lichens_Stand

The occurrence and dominance values of lichens species from the full stand inventory.

Table Lichens_Traits

The full names of the lichen species, their threat status (Artdatabanken 2020), growth form, reproductive strategy and spore volume (no data for asexual species lacking spores)

Table Logs

Information of sampled logs in the transect study including tree species, type of log, position along transect, maximum diameter, diameter at 4 m (if longer than 4 m), minimum diameter, length and decay stage. Further providing information on logs sampled for DNA analysis and whether DNA was extracted from the sample.

Table Points

Stand data (forest type, basal area of standing trees for each species and separated on living and dead trees) and age of dominant trees from the transect study where information was collected at 0, 50 and 100m along the transect. Forest types correspond to Hägglund & Lundmark 1994.

Table Transect

Coordinates of the transects (coordinate system Sweref99 TM) and number of old and recent cut stumps. 999 denotes missing data

Table WKH

Information on Woodland Key Habitat with Swedish names, inventory dates (transect and full stand inventories), centre coordinates (Sweref99 TM), and stand size.

References

Artdatabanken 2020. Rödlistade arter i Sverige 202. SLU, Uppsala

Atrena, A., Undin, M., Edman, M., Carlsson, F., Englund, O. & Jonsson, B.G. 2025. Fragmented forests, isolated fungi: saproxylic polypores in boreal woodland key habitats. Forest Ecology and Management, 596: 123065

Atrena, A., Kolényová, M., Samarakoon, J.M., Edman, M., Carlsson, F., Englund, O. & Jonsson, B.G. 2026.The effect of stand structure and landscape fragmentation on saproxylic polypores and epiphytic lichens in boreal Sweden. Forest Ecology and Management, in press

Atrena, A. 2025. Breaking up the boreal – the impact of forest fragmentation on wood fungi and lichens. PhD-thesis, Mid Sweden University, Sundsvall.

Bubnicki, J.W., Angelstam, P., Mikusiński, G. Svensson, J. & Jonsson, B.G. 2024. The conservation value of forests can be predicted at the scale of 1 hectare. Communications Earth & Environment, 5: 196

Hägglund, B. & Lundmark, J.-E. 1994. Handledning i bonitering. Del 3 Markvegetationstyper-Skogsmarksflora. Skogsstyrelsen, Jönköping.
Keywords: Woodland key habitats; Boreal forests; Saproxylic fungi; epiphytic lichens; Landscape structure; Biological Sciences; Biologi; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske